Behaviour change policy agendas for 'vulnerable' subjectivities: the dangers of therapeutic governance and its new entrepreneurs - Ecclestone, Kathryn (Journal of education policy, 2017)
Apocalyptic crisis discourses of mental health problems and psycho-emotional dysfunction are integral to behaviour change agendas across seemingly different policy arenas. Bringing these agendas together opens up new theoretical and empirical lines of enquiry about the symbioses and contradictions surrounding the human subjects they target. The paper explores the relationship between behaviour change policy, enduring philosophical and political scepticism about the viability of the rational, autonomous subject of liberal and neoliberal governance, and the contemporary cultural privileging of its vulnerable, anxious and stressed counterpart. Weber's accounts of authority illuminate dangers arising from an ad hoc, shifting, unaccountable state-sponsored intervention market that targets the vulnerable subject, proselytised by new types of 'therapeutic entrepreneurs'. Using an education-based example of statutory legislation for counter-terrorism in schools and universities, the Prevent strategy, the paper argues that jettisoning the rational, liberal subject has extremely worrying implications for education and democracy. It concludes with questions about the implications of these under-researched cultural and political phenomena for assumptions about the subjects of governance.